Struktur Modal dan UKM : A Systematic Literature Review - Ahyar, Muhammad; Fadah, Isti; Paramu, Hadi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This systematic literature review (SLR) aims to provide a comprehensive overview of the existing research on the impact of capital structure on small and medium-sized enterprises (SMEs). The study synthesizes and analyzes findings from various studies to identify key trends, gaps, and areas for future research. The SLR covers factors influencing SMEs' capital structure decisions, including internal factors like company size, profitability, and growth opportunities, and external factors such as market conditions, industry characteristics, and regulatory environment. Our findings reveal that the capital structure significantly affects SMEs' financial performance and sustainability. Debt financing offers growth potential but increases financial risk, while equity financing provides stability and reduces risk but dilutes ownership. The optimal mix of debt and equity varies based on specific SME characteristics and external conditions. Additionally, the capital structure influences SMEs' ability to attract external financing and impacts their overall growth and profitability. The review also highlights the need for more focused research on the determinants of capital structure in SMEs, the role of external financing sources, and the relationship between capital structure and firm performance over time. Longitudinal studies and investigations into macroeconomic factors' impact on SMEs' capital structure decisions are recommended for future research.